2019
DOI: 10.1055/s-0039-1696686
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism despite Ongoing Prophylaxis after Fast-Track Hip and Knee Arthroplasty: A Prospective Multicenter Study of 34,397 Procedures

Abstract: Introduction Venous thromboembolism (VTE) is a serious complication to total hip and knee arthroplasty (THA/TKA). However, recent publications found low 90-day incidences of VTE with in-hospital only thromboprophylaxis after fast-track THA and TKA, but with a subgroup with VTE despite thromboprophylaxis. Objectives We aimed to investigate in detail the incidence and risk for VTE despite ongoing thromboprophylaxis after fast-track THA and TKA. Materials and Methods This is a prospective unse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The lack of a direct and timely relationship between cement implantation and the occurrence of postoperative PE suggests that other factors, such as obesity and delayed mobilization, may also contribute (Table 4). Furthermore, many of the PE events happened despite ongoing thromboprophylaxis, indicating that these events happen in high-risk patients, requiring further investigations as discussed in detail by Petersen et al (2019). We therefore feel that the term "bone cement implantation syndrome" should be used with more caution in this context.…”
Section: Discussionmentioning
confidence: 98%
“…The lack of a direct and timely relationship between cement implantation and the occurrence of postoperative PE suggests that other factors, such as obesity and delayed mobilization, may also contribute (Table 4). Furthermore, many of the PE events happened despite ongoing thromboprophylaxis, indicating that these events happen in high-risk patients, requiring further investigations as discussed in detail by Petersen et al (2019). We therefore feel that the term "bone cement implantation syndrome" should be used with more caution in this context.…”
Section: Discussionmentioning
confidence: 98%
“…However, we found no correlation between anticoagulation interruption and DVT, which may be related to the risk of bleeding associated with anticoagulation interruption in this study. For patients hospitalized for total knee and hip replacement within 5 days, Samama et al, Petersen et al, and other large-sample, multi-center studies have confirmed that anticoagulation in these patients is safe only in the hospital [ 14 , 15 ]. However, there are few studies on the timing of anticoagulation after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,5 The risk of VTE after orthopedic surgery is 0.4%-1.0% despite the use of thromboprophylaxis, including minor orthopedic procedures. [6][7][8][9][10][11][12][13][14] This study's objective was to investigate the postoperative risk of VTE in all types of lower extremity orthopedic surgery compared with the background population to identify areas needing a more thorough investigation of potential use of thromboprophylaxis. We report 180-day cumulative incidences and hazard ratios (HRs) of VTE after orthopedic surgery in a matched, retrospective cohort study based on Danish national health care register data.…”
Section: Introductionmentioning
confidence: 99%